International air travel attitude and travel planning lead times across 45 countries in response to the COVID-19 pandemic. - Gallego-Galán, Inmaculada; González-Rodríguez, Rosario; Font, Xavier (Elsevier, 2022)
This paper explores global differences in travel risk perception based on i) attitudes towards travel abroad, and ii) the time required to plan travel. Baseline data from 2019 is compared with data from 2020, the first year of the COVID-19 pandemic. A methodology based on Big Data is developed through the Skyscanner metasearch engine, working with 20,756 million flight searches and 1979 million flight picks worldwide. We conduct an exploratory analysis by region, followed by a cluster analysis of 45 countries. We argue that the findings respond to uncertainty avoidance, with clear differences between Europe, America and Asia-Pacific. This knowledge has marketing implications for tourist destinations in terms of what marketing messages to convey and the best time to introduce marketing campaigns for each country or group of countries, so that the opportunity for reactivation of tourism is maximised.
Keywords: Pandemia de la Covid-19, 2020 - Aspectos sociales; Turismo - Efectos de la COVID-19; Aversion to travel; Lead times; Risk perception; Big data; Flights; COVID-19